2023
DOI: 10.3390/jcm12093143
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Stress and Anxiety in Pregnant Women Depending on Social Support and Physical Activity

Abstract: Social support and physical activity are mentioned among the numerous factors affecting the emotional state of pregnant women. Therefore, the aim of the study was to assess the level of perceived stress and anxiety in pregnant women depending on social support and their physical activity both before and during pregnancy and find the factors that affected the level of perceived stress. Methods. A total of 373 pregnant women were qualified for the study. The Perceived Stress Scale (PSS-10), the State-Trait Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In addition, physical activity before pregnancy and childbirth education is considered to be among the factors Human Movement, Vol. 25, No 1, 2024 that most significantly reduce perinatal anxiety [12]. In the group of active women surveyed during the COVID-19 pandemic, significantly higher stress levels and significantly worse moods were recorded compared to the physically inactive women.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, physical activity before pregnancy and childbirth education is considered to be among the factors Human Movement, Vol. 25, No 1, 2024 that most significantly reduce perinatal anxiety [12]. In the group of active women surveyed during the COVID-19 pandemic, significantly higher stress levels and significantly worse moods were recorded compared to the physically inactive women.…”
Section: Discussionmentioning
confidence: 94%
“…the main factors affecting the mood of a woman in the early postpartum period are hormonal changes, the presence of mood swings or depression in the past, as well as the presence of postpartum depression in the family history. Other important factors are lower socioeconomic status, teenage pregnancy, lack of education, unplanned or unwanted pregnancy, health complications of the woman during pregnancy and the need for hospitalisation, difficult childbirth and health problems of the newborn [7,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kowalska [ 33 ], social support is significantly related to the level of perceived stress and anxiety experienced by pregnant women. Findings from this study revealed that all three components of social support reduce the level of psychological distress though at different level.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…A form of psychological change in the third trimester is a form of irritable behaviour, easily sad, fear and anxiety (Kowalska, 2023).…”
Section: Introductionmentioning
confidence: 99%